Reconstruction of The Concept of Authority in Administrative Law Related to National Strategic Projects Based on Substantive Justice - Muh Ali Masnun; Dicky Eko Prasetio (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
The National Strategic Project (PSN) is one of the government's efforts to prosper society, although its implementation often causes problems in aspects of administrative authority, risk management, state finances, and the dimension of justice. To comprehensively analyze and integrate the aspects of administrative authority, risk management, state finance, and justice within a complete conceptual framework, particularly in the context of PSN. This research is a normative legal study with a conceptual and legislative approach. Discretion plays an important role in the implementation of PSN, although it must be carried out within the framework of legislation and the Principles of Good Governance (AUPB) as the basis for legitimacy and testing of administrative actions. In the context of PSN, characterized by high risk, high capital, and high discretion, there is a tension between the need for policy flexibility and the demand for state financial accountability, especially in distinguishing between policy risk and losses due to abuse of authority. Based on the perspective of substantive justice, the assessment of state losses should not rely solely on formal aspects but must also consider good faith, policy objectives, and their benefits to the public. Therefore, this research reconstructs the concept of administrative authority based on risk-based administrative justice, which integrates aspects of administration, state finance, and justice, thereby enabling the realization of a more adaptive, accountable, and substantively just use of authority.